Method to quantify the dynamic near-fault full-field stress evolution associated with rough fault shear deformation based on 3D printed models and photoelastic measurements. (15th February 2023) - Ju, Yang; Wan, Changbing; Dong, Shen; Mao, Lingtao; Wang, Kai; Chiang, Fu-pen
Highlights: A quantification method for dynamic full-field stress evolution is proposed. A fringe order counting method is developed to improve quantification efficiency. 3D printing technology is used to fabricate the rough fault models in shear tests. The full-field stress in a rough fault model under shear forces is quantified. The accuracy of the stress quantification method is theoretically verified. Abstract: Quantifying the dynamic near-fault stress evolution associated with fault shear deformation is crucial for revealing the earthquake nucleation mechanisms of rough faults. However, it is still challenging via traditional methods because of the difficulties in resolving continuously evolved stresses and high stress heterogeneity. In this study, we present a novel method to quantify the dynamic full-field stress evolution using three-dimensional printed models and photoelastic techniques. The dynamic full-field stresses in a circular disc determined by this method and an analytical model are compared to verify the accuracy of the proposed method. A new method to count the fringe orders near the rough fault is proposed to achieve the stress quantification. The full-field principal stress difference in a rough fault model under shear forces is derived. Our findings indicate that the proposed method can significantly improve the efficiency of stress calculation and effectively quantify the dynamic full-field stress near rough faults.